As Praças Centrais de Presidente Prudente-SP: avaliação do caráter como subsídio para intervenções projetuais - Bispo, Thaís Mitie Shiguematsu [UNESP] (2011)
During the process of development and urban sprawl in the city of Presidente Prudente (SP), some factors as the emergence of new centralities, the change in lifestyles and the expansion of equipments and urban infrastructure contributed to the dismantling and little appropriation of the central open space system. In this sense, the work is about the loss of continuity between the central squares of the city - Monsenhor Sarrion Square, July 9 Square, Bandeira Square and Nossa Senhora Aparecida Square - using different methodologies for character evaluation of each square, identifying the inviting and unattractive aspects of their spaces. The relations between these squares and its surroundings are characterized by analyzing interesting visual played on sketches, to complement character evaluation. Among these studies, it is also analyzed two spatial structures related to the squares – Calçadão and Quintino Bocaiuva Street - which have important architectural referring to the city's history and contribute to the central open space system configuration. General considerations obtained through diagnosis provided subsidies for the projectual proposed intervention, which aims to provide appreciation of the character of these public spaces and their articulation, promoting their use and constituting, thus, an important urban-environment set